If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4n + 1 + -5n = 6n + 7 + -9n Reorder the terms: 1 + 4n + -5n = 6n + 7 + -9n Combine like terms: 4n + -5n = -1n 1 + -1n = 6n + 7 + -9n Reorder the terms: 1 + -1n = 7 + 6n + -9n Combine like terms: 6n + -9n = -3n 1 + -1n = 7 + -3n Solving 1 + -1n = 7 + -3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '3n' to each side of the equation. 1 + -1n + 3n = 7 + -3n + 3n Combine like terms: -1n + 3n = 2n 1 + 2n = 7 + -3n + 3n Combine like terms: -3n + 3n = 0 1 + 2n = 7 + 0 1 + 2n = 7 Add '-1' to each side of the equation. 1 + -1 + 2n = 7 + -1 Combine like terms: 1 + -1 = 0 0 + 2n = 7 + -1 2n = 7 + -1 Combine like terms: 7 + -1 = 6 2n = 6 Divide each side by '2'. n = 3 Simplifying n = 3
| 4b+8=7b-4 | | -6f=-36 | | 3x-1=5x+7 | | 15a-10=20a | | (2/5)+x=(-1/10) | | -6(18+3y)=-9 | | (2n+2)(2n-2)= | | 14x-(10x-3)=17 | | (2/5)+=(-1/10) | | 13+(-15x)=74-12 | | (2n^2+2)(2n-2)= | | 2n+7n-28=26 | | 12x-5x=49 | | 12=3t | | 3xy+5x+2xy-8x= | | 14=2p | | 2/3(n-3)=1/3(n+6) | | 12(3x+4)-7=2x-23 | | ln(x)+ln(2)=3 | | -(-9x)=(-48) | | 5-4m-5m=m-4m+2 | | 6x-4y+x-5y= | | y=.5x-4 | | 14=2b | | y=-2.2x-5 | | 6x-8=2(x-4) | | 8xy-2xy= | | p+4-5=3p-8-7p | | 5x-8x+2x= | | (-6)-(2)-(-3)= | | 8q=38 | | (-8)+(-2)+(-5)= |